Description of Methadone Dose Usage of Methadone Maintenance Therapy Program Patients - Amran, Melwani; Ramatillah, Diana Laila (Journal La Medihealtico, 2024)
Methadone treatment is the most common treatment for opioid dependence, methadone replaces opioids with an adjusted dose. The dose is gradually reduced over a period of time, and you can eventually stop taking methadone. The purpose of this study was to determine the dose of methadone given to patients in the Methadone Maintenance Therapy Program (PTRM) in the Greater Tangerang area from January to December 2023. Methadone clinics in Greater Tangerang are Cibodasari Health Center, Cipondoh Health Center, and Ciputat Health Center. This study was conducted using a cross-sectional method with a descriptive approach. Based on a survey of 33 patients receiving methadone maintenance therapy, the characteristics of the patients were as follows: 30 men (91%), 3 women (9%), 32 people (97%) aged 25 to 45 years, and 46 years - 55 years as many as 1 person (3%), junior high school education 6 people (18%), high school education 19 people (58%), bachelor's degree qualification 5 people (15%) university 3 people (9%), married 24 people (73%), 4 people unmarried (12%) and 5 people married (15%). The initial maintenance dose for treatment is 15 to 30 mg per day. The minimum maintenance dose is 0.7 mg per day. The highest maintenance dose is 210 mg per day. The average maintenance dose is 76.13 mg per day. Based on the results of this study, it can be concluded that 33 patients who received therapy were in accordance with the PTRM guidelines with maintenance doses usually ranging from 60 to 120 mg / day.